Treatment of Unruptured Cerebral Artery Aneurysm: A Meta-Analysis: Life Sciences-Neuro surgery for better health care - Fatema Turkistani; Aseel Bin Sawad (International Journal of Life Science and Pharma Research, 2022)
Unruptured middle cerebral artery (MCA) aneurysms can be treated using two techniques or procedures, microsurgical clipping and endovascular coiling. The aim of this meta-analysis study is to compare the safety and efficacy of microsurgical clipping with the endovascular coiling in the treatment of unruptured MCA aneurysms. We searched electronic databases (PubMed, EMBASE and the Cochrane library) to identify studies published between 1991 and 2019. For clipping and coiling techniques, separate meta-analyses were conducted on efficacy and safety after the intervention and at follow-up by using random- and fixed-effects models. Forty-one articles were included in our meta-analyses: 23 case series using clipping and 25 case series using coiling procedures. The complete aneurysm occlusion rate was higher in the clipping procedure (96.1%, 95% CI: 92.8%-97.9%) as compared to the coiling procedure (57.6%, 95% CI: 49.4 – 65.4%). Clipping procedure has a slightly higher rate of favorable functional outcomes (96.4%, 95% CI: 94.8 – 97.5%) compared to coiling procedure (94.8%, 95% CI: 93.1 –96%). Interestingly, the rate of occlusion appears to decrease with time in the clipping group and increase with time in the coiling group, while the rate of favorable functional outcomes appears to increase with time in the clipping group and decrease with time in the coiling group. Publication bias was unlikely in all our analysis for studies assessing: coiling and occlusion rate, clipping and occlusion rate, coiling and functional outcomes, and clipping and functional outcomes. Microsurgical clipping yields a higher aneurysm occlusion rate, with slightly higher favorable functional outcomes in the treatment of unruptured MCA aneurysms than the endovascular coiling.